Beyond the Balance Sheet: Investigating the Association Between NHA Turnover and Nursing Home Financial Performance - Pradhan R; Ghiasi A; Davlyatov G; Orewa GN; Weech-Maldonado R (Dove Medical Press, 2024)
Rohit Pradhan,1 Akbar Ghiasi,2 Ganisher Davlyatov,3 Gregory N Orewa,4 Robert Weech-Maldonado5 1School of Health Administration, Texas State University, San Marcos, TX, USA; 2Healthcare Administration Department, University of the Incarnate Word, San Antonio, TX, USA; 3Health Administration & Policy, University of Oklahoma Health Sciences Center, Oklahoma City, OK, USA; 4Department of Public Health, University of Texas at San Antonio, San Antonio, TX, USA; 5Department of Health Services Administration, University of Alabama at Birmingham, Birmingham, AL, USACorrespondence: Rohit Pradhan, Email pradhan@txstate.eduIntroduction: Nursing homes (NHs) serve as a safety net for vulnerable populations such as older adults and people with disabilities. Nursing Home Administrators (NHAs) play a crucial role in managing the daily operations of NHs, including overseeing direct care staff and establishing the facility's strategic direction. Unfortunately, NHs have consistently faced high NHA turnover rates, which have been linked to poor organizational performance. This study aims to investigate the relationship between NHA turnover and financial performance in NHs.Methods: Using an integrated perspective based on the upper echelons theory and the resource-based view of the firm, we investigated the association between NHA turnover and financial peformance using multiple secondary data sources, such as the Care Compare: Skilled Nursing Facility Quality Reporting Program and Brown University's Long Term Care Focus. We conducted a cross-sectional study using a multivariate linear regression model, measuring financial performance using operating margin while NHA turnover represents the number of administrators that left the organization.Results: Our findings indicate that NHs with higher NHA turnover rates have lower operating margins. Specifically, compared to facilities with no turnover, one NHA turnover is associated with a 1.14% decrease in operating margin, and two or more turnovers are associated with a 2.25% decrease.Discussion: This study contributes to the existing literature by demonstrating the financial impact of NHA turnover and provides further evidence of the need for targeted organizational and policy interventions to improve NHA retention.Keywords: nursing homes, administrators, turnover, financial performance